Application for Electronic Services in Malang City Based on Android - Wibowo, Dimas Wahyu; Pramitarini, Yushintia; Bramantya, Aliefian Dio (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Most people have electronic units. Electronic units also have advantages and disadvantages. As the advantages, electronic is that it can simplifies human-work, for example, people used to wash their clothes in a bare hand. Since the existence a washing machine, people only need to put dirty clothes into the tub then the wash-machine does the rest. For the disadvantages, electronics have an expiration date. If the electronics are on the expiration period, the performance decreased. The problem can overcome by repairing the stuff. If someone cannot to repair electronics the item itself, then requires someone else who is capable to solve it in the field. To ease the time looking for services that are nearby to the user’s current location is possible. The system has been implemented on smartphone devices with an Android and Web-connected to the internet. The system help users to get information on the location of the nearest electronic service service and display service progress in realtime.The results provide a reference to the implementation of the Haversine Algorithm for distance calculation formula using GPS on an Android smartphone. This system proposes a solution as a liaison between service buyers and service providers. For electronic service providers can be used as a medium for promotion. The application is convenience in getting the nearest location for service, displays the service progress and with distance and location information features in this system can provide a reference for buyers of electronic services.